Mutations in plasmalemma vesicle-associated protein cause severe syndromic protein-losing enteropathy. Issue 9 (16th April 2018) - Broekaert, Ilse Julia; Becker, Kerstin; Gottschalk, Ingo; Körber, Friederike; Dötsch, Jörg; Thiele, Holger; Altmüller, Janine; Nürnberg, Peter; Hünseler, Christoph; Cirak, Sebahattin
Abstract : Background: Protein-losing enteropathy (PLE) is characterised by gastrointestinal protein leakage due to loss of mucosal integrity or lymphatic abnormalities. PLE can manifest as congenital diarrhoea and should be differentiated from other congenital diarrhoeal disorders. Primary PLEs are genetically heterogeneous and the underlying genetic defects are currently emerging. Objectives: We report an infant with fatal PLE for whom we aimed to uncover the underlying pathogenic mutation. Methods: We performed whole exome sequencing (WES) for the index patient. Variants were classified based on the American College of Medical Genetics and Genomics guidelines. WES results and our detailed clinical description of the patient were compared with the literature. Results: We discovered a novel homozygous stop mutation (c.988C>T, p.Q330*) in the Plasmalemma Vesicle-Associated Protein ( PLVAP ) gene in a newborn with fatal PLE, facial dysmorphism, and renal, ocular and cardiac anomalies. The Q330* mutation is predicted to result in complete loss of PLVAP protein expression leading to deletion of the diaphragms of endothelial fenestrae, resulting in plasma protein extravasation and PLE. Recently, another single homozygous stop mutation in PLVAP causing lethal PLE in an infant was reported. Conclusions: Our findings validate PLVAP mutations as a cause of syndromic PLE. Prenatal anomalies, severe PLE and syndromic features may guide the diagnosis of this rare disease.